Co-opetition in next-generation access provisioning: An analysis of the German broadband market - Felix Limbach; Ruediger Zarnekow; Michael Düser (International Telecommunications Society (ITS), 2012)
The growing customer demand for next-generation access networks requires large investments into novel broadband infrastructures. Politicians, scientists and practitioners have been discussing the question if cooperation between today's broadband carriers can contribute to a cooperative setup of next-generation access networks. In order to advance this discussion we asses horizontal, vertical and diagonal cooperation between today's carriers based on a grounded theory approach. We base our findings on more than twenty-five expert interviews in eleven telecommunication companies of the German broadband market. Our results indicate that cooperation is currently primarily evolving at vertical and diagonal cooperation interfaces. Moreover, the German broadband provisioning market is heading towards a continuously deconstructed telecommunication value chain and standardized wholesale products which are primarily offered at vertical and diagonal cooperation interfaces.
Keywords: 330